Pengaruh Penggunaan Media Pembelajaran Berbasis VBA For Excel Terhadap Motivasi Siswa SD Pada Materi Bangun Datar - Vina Novianti; Nurul Sa'adah; Siti Chotimah (Journal on Education, 2019)
This study aims to describe the learning motivation of elementary students who use ICT VBA Excel learning media on flat material. This research uses descriptive qualitative method. This research was conducted with a sample of 22 elementary school students in West Bandung Regency. The instrument used was in the form of a student learning motivation scale questionnaire that contained 25 statements and 4 answer choices, namely 1. Very Agree (SS), 2. Agree (S), 3. Disagree (TS) and 4. Very Disagree (STS). The questionnaire used is related to Excel VBA learning media which have 6 indicators. The results showed that an elementary student learning process that uses the VBA Excel learning media on flat material overall is classified as good, there are 2 indicators that qualify very well, namely indicators of confidence in using mathematics (Very Good); Indicators can maintain opinions (very good). There is one indicator that includes good criteria, namely indicators Perseverance in doing mathematics (Good). There are 3 indicators that fall into sufficient criteria, namely Flexible indicators in doing mathematical work (Enough), indicators of Willingness to leave